2022
DOI: 10.1002/ecs2.4138
|View full text |Cite
|
Sign up to set email alerts
|

Use of marine vs. freshwater proteins for egg‐laying and incubation by sea ducks breeding in Arctic tundra

Abstract: Understanding dietary nutrient sources is fundamental to conserving sensitive species, especially as climate change alters food web dynamics. Migratory species that depend on both marine and terrestrial habitats face unique challenges, as the locations and quality of resources in the two realms may respond quite differently to environmental changes, with potential for spatial and temporal carryover effects. For sea ducks (Mergini) that winter at sea but move inland to breed, body size may determine their capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…Chironomidae larvae comprised the largest and most consistent fraction of available relative biomass density (67%-85% in cores, and 50%-74% in sweeps; Table 3), with no other single taxon comprising ≥20% of total biomass density. This pattern of relative total biomass differed from the pattern in diets of adult female sea ducks (Miller et al, 2022). Insect larvae (mostly chironomids) comprised only 4%-14% of protein sources for egg production but comprised 48%-90% of invertebrate biomass in cores and 47%-82% in sweeps (Table 3).…”
Section: Invertebrate Biomass Density and Duck Use Of Different Wetla...mentioning
confidence: 85%
See 4 more Smart Citations
“…Chironomidae larvae comprised the largest and most consistent fraction of available relative biomass density (67%-85% in cores, and 50%-74% in sweeps; Table 3), with no other single taxon comprising ≥20% of total biomass density. This pattern of relative total biomass differed from the pattern in diets of adult female sea ducks (Miller et al, 2022). Insect larvae (mostly chironomids) comprised only 4%-14% of protein sources for egg production but comprised 48%-90% of invertebrate biomass in cores and 47%-82% in sweeps (Table 3).…”
Section: Invertebrate Biomass Density and Duck Use Of Different Wetla...mentioning
confidence: 85%
“…Our sampling was inadequate to quantify the biomass density of oligochaetes, which stable isotope studies later revealed could be important prey for sea ducks (14%-52% of the diet for the four species studied here, Miller et al, 2022). Oligochaetes vary widely in their relative size and are often considered meiofauna; thus, they are not sampled well by a 0.5-mm sieve which we used as the accepted standard for macroinvertebrate sampling (Higgins & Thiel, 1988;Hummon, 1981;Nalepa & Robertson, 1981).…”
Section: Invertebrate Sampling and Biomass Estimationmentioning
confidence: 99%
See 3 more Smart Citations